2014
DOI: 10.3892/mmr.2014.2320
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of hypoxia-inducible adrenomedullin using RNA interference attenuates hepatocellular carcinoma cell growth in vivo

Abstract: Adrenomedullin (ADM) is an angiogenic peptide that has been shown to increase the risk of endometrial hyperplasia and to promote tumor cell survival following hypoxia. ADM may induce microvessel proliferation and partially decrease hypoxia in solid tumors, thus contributing to the proliferation of tumor cells, as well as tumor invasion and metastasis. However, the impact of hypoxia‑induced ADM expression on hepatocellular carcinoma (HCC) cells requires further elucidation. In the present study it was found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Furthermore, It was observed that AM could be an upstream modulator of the HIF-1a/VEGF pathway, suggesting that AM might induce angiogenesis through VEGF expression as consequence of JNK and AP-1 activation in epithelial ovarian cancer (6,7). Analogously, several in vitro and in vivo studies have demonstrated the involvement of hypoxia, HIF-1a, AM, and AM receptors in HCC development, and how anti-AM therapeutic approaches would be of great value to deal with this disease (164)(165)(166).…”
Section: Roles Of Am In Cancermentioning
confidence: 97%
“…Furthermore, It was observed that AM could be an upstream modulator of the HIF-1a/VEGF pathway, suggesting that AM might induce angiogenesis through VEGF expression as consequence of JNK and AP-1 activation in epithelial ovarian cancer (6,7). Analogously, several in vitro and in vivo studies have demonstrated the involvement of hypoxia, HIF-1a, AM, and AM receptors in HCC development, and how anti-AM therapeutic approaches would be of great value to deal with this disease (164)(165)(166).…”
Section: Roles Of Am In Cancermentioning
confidence: 97%
“…Adrenomedullin (ADM) has the ability to induce microvascular proliferation of solid tumors and promote tumor proliferation and migration (33). Knockdown of ADM can increase the sensitivity of cisplatin to hepatoma cells (34). TNF alpha induced protein 3 (TNFAIP3) can induce EMT and promote metastasis in most tumors (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma cells express AM and its receptor and, under hypoxic conditions, favor AM expression [ 226 ]; in addition, AM mRNA, HIF-1α and VEGF levels were increased under the same conditions in human hepatocellular carcinoma cell lines [ 229 ]. CLR, RAMP2, and RAMP3 have been reported in liver cancer, and a high AM level has been related to increased intrahepatic metastasis [ 226 , 227 ].…”
Section: Involvement Of the Tachykinin And Calcitonin/calcitonin Gene...mentioning
confidence: 99%
“…AM, through Akt activation, promoted the growth of hepatocellular carcinoma cells, which was inhibited with AM inhibitors [ 226 ]. Knockdown of AM expression promoted apoptotic mechanisms in hepatocellular carcinoma cells and, combined with cisplatin, significantly decreased tumor growth when compared with knockdown of AM expression or cisplatin alone [ 229 ]. The data show the association of AM with hepatocellular carcinoma development.…”
Section: Involvement Of the Tachykinin And Calcitonin/calcitonin Gene...mentioning
confidence: 99%
See 1 more Smart Citation